Clinical assessment and examination in orthopaedics - Rex, C.; Rajasekaran, S.; Galasko, Charles SB (New Delhi : Jaypee Brothers Medical Publishers, 2012)
Guía práctica paso a paso para la evaluación clínica y el examen en ortopedia, que cubre todas las áreas del cuerpo y las pruebas de diagnóstico clínico relevantes.
Practical, step by step guide to clinical assessment and examination in orthopaedics, covering all areas of the body and relevant clinical diagnostic tests.
Contents 1. History taking and clinical examination 2. Examination of injured patient 3. Examination of patient with bone and joint injuries 4.Examination of neuromuscular disease 5. Examination of shoulder y otros 9 capítulos más
Keywords: ORTOPEDIA; ORTOPEDIA -- DIAGNÓSTICO; SISTEMA MUSCULOESQUELÉTICO -- ENFERMEDADES -- DIAGNÓSTICO; ORTHOPEDICS -- DIAGNOSIS